Projeto de controle de alocação tolerante a faltas para um veículo autônomo subaquático utilizando lógica nebulosa - Cardozo, Daisy Isabel Kang (2013)
In critical systems such as airplanes, space ships, underwater vehicles, nuclear power plants, among others, failures and faults can bring catastrophic consequences. Therefore, it is required to take into account possibilities of degradation in the performance of its components. This work presents a fault-tolerant control for the propulsion system of the BA-1, an Autonomous Underwater Vehicle (AUV), by using a Fuzzy Allocation Control. This methodology takes advantage of thrusters redundancy, common in autonomous vehicles, to relocate the available thrusters forces in failure situations. That is, it performs an on line reconﬁguration of the thrusterforce allocation matrix in the pseudo inverse method. This approach was tested for all the possible cases of horizontal failure of the BA-1 vehicle by means of numerical simulations.Two cases were studied for each failure situation over a linear trajectory in the x axis; the ﬁrst one studies the case where failures occurs when the vehicle starts its trajectory; and the second one studies the case where the vehicle suffers failures while travelling in its maximum speed.The studies show that the vehicle has an acceptable behavior on most situations, except when it suffers failures of two thrusters which are parallel to the x axis when travelling at maximum speed. However that problem could be solved if the reference trajectory is modiﬁed after the failure occurs. In all, the control system developed presents quick responses and an acceptable degradation of performance.